PERFORMANCE MEASUREMENT ANALYSIS WITH BALANCE SCORECARD METHOD ON SDIT NURUL AKBAR KLATEN - Eka Mustika Anggraini; Johny Subarkah; Muhammad Hasan Ma'ruf (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to measure performance using the Balance Scorecard method at SDIT Nurul Akbar Klaten. This research is included in quantitative research. The population of this study were all students and teachers of SDIT Nurul Akbar Klaten. The samples collected in this study were 52 respondents for students and 30 respondents for teachers. The sample selection technique is using purposive sampling where the sample is determined based on certain criteria. The data used is primary data where data is obtained from respondents' answers through a questionnaire that has been given. SPSS is used in research as an analytical tool. The results of this study indicate that (1) Finance has a positive and significant influence on company performance. (2) Customers have a positive and significant influence on the Company's Performance. (3) Internal business processes have a positive and significant impact on Company Performance. (4) Growth and Learning have a positive and significant impact on Company Performance